CLIL PRACTICES IN TOMSK POLYTECHNIC UNIVERSITY: SUCCESSES AND FAILURES - T. V. Sidorenko; S. V. Rybushkina; Ya. V. Rosanova (Образование и наука)
Introduction. Content and Language Integrated Learning (CLIL) has recently been applied into education system, but a range of supporters is rapidly increasing, covering diverse countries. The CLIL approaches simultaneously use a foreign language as an object to studying and as an instrument to learning other subjects. The emergence of CLIL was related to a wide distribution of bilingualism in society and the need to cope with the problems related to this process, including the elimination of international conflicts, the consolidation of society as the factor of a social well-being, the support of a competitive labour market, etc.Despite growing popularity of CLIL across the world and recognised status by the European Union as one of the leading effective means to implementing international language policy of multilingualism, the academic teaching staff of Russian higher school does not still fully understand the organisational mechanisms and forms of a similar learning process, largely as a result of national characteristics and traditions. In a globalising world, CLIL didactics is currently becoming a perspective direction of higher education and an effective way both of acquiring and improving language and communicative competencies to provide further successful professionalising of students and to facilitate their career promotion in the chosen field of activity.The aim of this paper was to sum up and discuss the experience of Tomsk Polytechnic University in conducting CLIL-based courses.Methodology and research methods. The concept of practice-oriented vocational education was used as the methodological base of the experimental work in order to search optimal variants when developing foreign language knowledge in the students of engineering specialties. In the course of the research, the approaches of comparative analysis, synthesis, generalisation, forecasting, design, modelling, prolonged monitoring of learning outcomes, observation and questionnaire survey were applied. Results and scientific novelty. The actualising reasons for CLIL approach in the Russian high school education were formulated and proved. The brief historical overview of didactic concepts was presented. The authors analysed temporary challenges which preceded the implementation of CLIL methodologies in the learning process of Tomsk Polytechnic University (TPU) and the introduction of programme “Vocational Training and Education in a Foreign Language” (3rd-4th years of education). The stages of teaching foreign language evolution at the university were distinguished: the anglification of engineering education transformed into multidisciplinary model of English for Specific Purpose (ESP); the creation of “pedagogical tandems” – the organization of courses with “double agents”; and, finally, CLIL training in which a cognitive component can be seen as the key characteristic and the main advantage. Success and failure in the field of CLIL practices available today at TPU were revised. The examples of private implementable practices were described and analysed. The research findings revealed the rationality when using various applied variations of CLIL methodology.Practical significance. The research outcomes allowed the authors to adjust not only the main educational programmes of higher education institution, but also internal programmes of professional development of teachers. Although the long-term experiment summarised in the publication in a single higher education institution does not apply for universality and mass circulation, the authors believe that experimentative materials will contribute to consistent embedding of CLIL courses into a complete system of vocational training.